Late Paleocene to early Oligocene fire ecology of the south Mongolian highland - Zhou, Xinying; Wang, Jian; Li, Qian; Bai, Bin; Mao, Fangyuan; Li, Xiaoqiang; Wang, Yuan-Qing (Frontiers in Earth Science, 2023)
Changes in fire ecology during warm and cold periods in the geological past are important because of their effects on terrestrial ecosystems and the global carbon cycle. We used the charcoal concentrations of the Erden Obo section in Inner Mongolia to reconstruct the evolution of wildfire and their relationship to the regional vegetation from the Late Paleocene through Early Oligocene. Our data show that fire frequency was relatively high from the end of the Paleocene to the beginning of the Eocene, in accord with other paleofire records worldwide. However, low fire frequency occurred during the Early Eocene Climate Optimum (EECO), coincident with the change in the regional vegetation from shrubland to forest due to the strengthening of the regional rainfall, and we suggest that the humid climate may have been responsible for this decrease. High frequency fire occurred after the Middle Eocene, near-synchronously with the transition of the regional vegetation from forest to steppe. The high- frequency fire were most likely triggered by regional drought during the aridification process after the Middle Eocene. We propose that these temporal changes in the fire ecology were consistent within the northern temperate zone from the Late Paleocene through Early Oligocene, and we suggest that studies of global wildfires need to be evaluated within the context of paleovegetation zones and ecosystem evolution.